PENDAMPINGAN IDENTIFIKASI POTENSI PENGEMBANGAN AGROWISATA BERBASIS PARTISIPASI MASYARAKAT DI DESA SUNGAI BESAR KECAMATAN KARANG INTAN KABUPATEN BANJAR KALIMANTAN SELATAN - Fitri Mahyudi; Husinsyah (INSPIRASI: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2024)
Sungai Besar Village is located enroute the Parangtritis Beach, which is one of the main tourist destinations in the Banjar Region of Kalimantan Selatan. This village has the potential to develop into an agro-tourism area based on the natural resources and community participation. Presently, community-based agro-tourism is being developed in this area through the Gadjah Mada University Assisted Villprogram. Therefore, this programme aims to 1) Identify the potential of natural resources and village landscapes; 2) Increase community participation in developing villages; and 3) Empower natural resources and village communities for agro-tourism development. Data were obtained from community participation- based agro-tourism planning using the Business Model Canvas (BMC) method and the Training on Trainer system from September 2024. Furthermore, during the Covid 19 pandemic, tourism education was carried outusing an online method such as Google meet and whatsapp group platforms. Potential identification carried out by the community in Sungai Besar Village shows the potential for natural resource attractions based on tourism development. Furthermore, various natural resources as the potential of agro-tourism attractions have started to be empowered, including plant nurseries in the yard (pekarangan), peanut brittle, gula semut, and banana weevil chips well as a homestay. Therefore, the coordination of the inter-hamlet agro-tourism program at the village level still needs to be improved.